KINERJA BADAN PENGAWAS PEMILU KOTA BATAM DALAM PENANGANAN PELANGGARAN PEMILU SERENTAK TAHUN 2019 DI KOTA BATAM - Limbong, Anita Sakdiah; Lodan, Karol Teovani (LPPM Universitas Putera Batam, 2020)
Simultaneous general election is a means of implementing people's sovereignty to elect the executive and legislative which are held together, on the same day, date, time. But in practice, there are election violations which are contradictory actions, violating the Election Law , this is the responsibility of the Election Supervisory Board . Thus the aim of researchers is to find out how the Performance of the Batam City Election Supervisory Body in Handling 2019 Concurrent Election Violations in Batam City with indicators of productivity, service quality, responsibility, responsiveness , and accountability. The research method is descriptive qualitative method to explain, illustrate provide an understanding of Bawaslu Performance . The results of this study indicate that Bawaslu's performance in handling simultaneous election violations is in accordance with Law No. 7 of 2017 Regarding general elections, there is a timeframe for handling violations and there is no authority of Bawaslu to summon reported parties. Lack of socialization and lack of operational facilities due to lack of budget. Thus the researcher concludes that the performance of the Batam City Election Supervisory Board in handling simultaneous election violations in Batam City has been maximiz.